2020
DOI: 10.3389/fneur.2020.586905
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Suppressors of Cytokine Signaling-3 (SOCS3) Expression Promotes M2 Macrophage Polarization and Functional Recovery After Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is a fatal subtype of stroke, and effective interventions to improve the functional outcomes are still lacking. Suppressor of cytokine signaling 3 (SOCS3) plays critical roles in the inflammatory response by negatively regulating cytokine-Jak–Stat signaling. However, the role of SOCS3 in the regulation of macrophage polarization is highly controversial and the fine regulation exerted by SOCS3 needs further understanding. In this study, rat ICH models were established by infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The JAK-STAT pathway has also been associated with ICH progression in rat models (Ji et al, 2020). Our GSEA results also showed that STAT3, which is closely related to mRNA catabolism, is a key gene leading to ICH.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The JAK-STAT pathway has also been associated with ICH progression in rat models (Ji et al, 2020). Our GSEA results also showed that STAT3, which is closely related to mRNA catabolism, is a key gene leading to ICH.…”
Section: Discussionsupporting
confidence: 66%
“…Previously, researchers found that miRNAs/mRNAs changes in whole-blood samples for patients with ICH were important links with the JAK-STAT pathway ( Cheng et al, 2020 ). The JAK-STAT pathway has also been associated with ICH progression in rat models ( Ji et al, 2020 ). Our GSEA results also showed that STAT3 , which is closely related to mRNA catabolism, is a key gene leading to ICH.…”
Section: Discussionmentioning
confidence: 99%
“…[46] SOCS1 improved M2 polarization, while SOCS3 promoted M1 polarization and prevented M2 polarization. [47,48] As shown in Figure 3g, qRT-PCR analysis revealed that HATLH considerably increased the mRNA expression of SOCS1 but decreased the mRNA expression of SOCS3 on M0 macrophages. These data demonstrated that HATLH excellently repolarized M0 to M2, thus facilitating the inhibition of the inflammatory microenvironment after spinal cord damage.…”
Section: The Effect Of Hatlh On Macrophages and Neural Precursor Cell...mentioning
confidence: 85%
“…A recent study has shown that Spp1 , Top2a , and Mki67 played a vital role in the inflammatory response during brain ischemic injury ( 48 , 49 ) and that Ptx3 was an important target in brain ischemic injury and possibly other brain inflammatory disorders ( 50 ). Some other findings indicated that the downregulation of Socs3 in the microglia/macrophages could lead to a marked bias toward the M2 phenotype and ameliorate the inflammation, which could promote neuroprotective effects after stroke ( 51 ). Therefore, this suggests that ischemic injury-associated genes play different roles in different tumor environments.…”
Section: Resultsmentioning
confidence: 99%